2009
DOI: 10.1093/brain/awp087
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N-acetyl-aspartyl-glutamate and N-acetyl-aspartate on white matter oligodendrocytes

Abstract: Elevations of the levels of N-acetyl-aspartyl-glutamate (NAAG) and N-acetyl-aspartate (NAA) are associated with myelin loss in the leucodystrophies Canavan's disease and Pelizaeus-Merzbacher-like disease. NAAG and NAA can activate and antagonize neuronal N-methyl-D-aspartate (NMDA) receptors, and also act on group II metabotropic glutamate receptors. Oligodendrocytes and their precursors have recently been shown to express NMDA receptors, and activation of these receptors in ischaemia leads to the death of oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Impaired NAAG signaling has been implicated in schizophrenia and some studies have suggested NAAG plays a role in antipsychotic drug mechanisms of action (Ghose et al, 2009; Olszewski et al, 2012; Jessen et al, 2013). Of particular relevance to our current study, elevated NAAG has been associated with hypomyelination disorders such as Canavan's disease and Pelizaeus-Merzbacher disease (PMD) (Kolodziejczyk et al, 2009). Symptoms of these disorders include a diminished motor control.…”
Section: Discussionmentioning
confidence: 89%
“…Impaired NAAG signaling has been implicated in schizophrenia and some studies have suggested NAAG plays a role in antipsychotic drug mechanisms of action (Ghose et al, 2009; Olszewski et al, 2012; Jessen et al, 2013). Of particular relevance to our current study, elevated NAAG has been associated with hypomyelination disorders such as Canavan's disease and Pelizaeus-Merzbacher disease (PMD) (Kolodziejczyk et al, 2009). Symptoms of these disorders include a diminished motor control.…”
Section: Discussionmentioning
confidence: 89%
“…Such changes in glutamate homeostasis have been implicated in mediating excitotoxicity (Matute 2011; Pitt et al 2003). However, it has also been suggested that mature rodent as well as human oligodendrocytes are largely resistant to such glutamate-mediated injury (Kolodziejczyk et al 2009; Rosenberg et al 2003; Wosik et al 2004). Thus, and in light of our findings, it is tempting to speculate that changes in glutamate homeostasis and sodium-dependent glutamate transporter signaling may primarily contribute to the differentiation block seen in MS rather than mediate oligodendrocyte cell death.…”
Section: Discussionmentioning
confidence: 99%
“…NAAG was indeed recently reported to have a negligible action on oligodendrocytes' NMDA receptors. 9 The increase of NAAG in the extracellular space resulting from inhibition of GCPII has also been shown to be neuroprotective. 10 In patients with undiagnosed leukodystrophies, increased free sialic acid in CSF or urine suggests the diagnosis of SASD.…”
Section: Increase Of Naag In the Csf Of Patients With Sasdmentioning
confidence: 99%